001: EHEALTH, TRADE POLICY & SOCIAL ACCOUNTABILITY. (24th August 2015) - Ann Wiley, Elizabeth; Loh, Lawrence Chew; ,; Gopfert, Anya PN
Abstract : Background: Over the last several years, a new generation of multilateral trade agreement negotiations has emerged. With a focus on regulatory harmonization and reductions in non-tariff trade barriers, the Transatlantic Trade Investment Partnership (TTIP), the Trans Pacific Partnership (TPP) and Trade in Services Agreement (TiSA) seek to advance trade liberalization and increase economic growth. These agreements aim to establish a new global framework for trade governance with broad potential implications for research and innovation for health around the world. With more than forty countries representing more than half of the global GDP participating, the potential economic power of these agreements is substantial. On a truly global scale, the TPP, TTIP and TiSA could profoundly affect the future of ehealth. Objectives: (1) Describe potential implications of current trade agreement negotiations on ehealth using a social accountability framework; and (2) promote ehealth and social accountability in current trade agreement negotiations. Methods: In this context and using a social accountability lense, this presentation analyzes potential implications of current negotiations on several dimensions of ehealth including (1) the provision of health care services (including telemedicine); (2) access to innovation and medical knowledge; and (3) health professional education and training. Result: Given the ongoing evolution and expansion of ehealth and its vast potential to advance health equity, it is essential that this next generation of trade agreements protect and promote rather than undermine access to health care services and progress toward universal health coverage. Conclusion: To this end, potential strategies and recommendations to promote ehealth and social accountability in trade agreement negotiations will be presented.